Exploring the Architecture of Place in America’s Farmers Markets - Albright, Kathryn Clarke (Book collections on Project MUSE., 2020)
"This book draws attention to the simple but elusive architectural space of public and farmers markets. It discusses three seminal types of markets--heritage building, open-air pavilion, and pop-up canopy-- demonstrating the characteristics of each type using a mixture of narrative and illustration. The narrative combines historically informed architectural observation with interview material drawn from conversations the author has had over the years with market managers, vendors, and shoppers. The illustrations include an appealing variety of photos, diagrams, and drawings that enabled the author to view each market through an architectural lens based on eight scales of measure--the hand, the container, the person, the stall, a grouping of stalls, the street, the block, and the market's situation within the neighborhood. Some of the architectural elements discussed include walls that layer, openings that frame, roofs that encompass, and niches that embrace. While each of the case studies illustrates shared characteristics of one of the architectural typologies, each farmers market is distinct in the specific ways it reflects the local culture and environment. Ultimately, in viewing markets through these three types and eight scales of measure we are able to better appreciate how farmers markets foster social interaction and community engagement"--